Modifikasi Sifat Mineralogi dan Fisiko-Kimia Bahan Tanah Vertik dengan Ball Mill Berenergi Tinggi - Joko Priyono; Ismail Yasin; Bustan Bustan (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
test of modifying the properties of vertic material by using a ball milling technique was carried out with the primary aim to eliminate the vertic (swelling-shrinking) property and increase the electrical charge of the material. The clay fraction of Vertisol was dried and ball milled for 5, 10, and 20 minutes. Results reveal that the clay fraction of the soil material was dominated by montmorillonite mineral, and ball milling for > 5 minutes transformed the crystalline montmorillonite into amorphous (non-crystalline) particles. Those changes were followed by increasing the vertic features, cation exchange capacity, water holding capacity, and suspension effect of the milled material. The improvement of vertic characteristics might be due to the increase of electric charge of the milled particles. Thus, high-energy ball milling was an effective technique to improve the reactivity and vertic property of vertic material of Vertisols. Further studies are needed to evaluate the potential uses of modified vertic materials as ceramic material, cement component, adsorbent of heavy metals, and other contaminants, or catalysator